Integration of microfluidics and nanoezyme peroxidase for colorimetric detection of neurotransmitters - Sousa, Cristina (2024)
The integration of Microfluidics and Nanozyme peroxidase for the Colorimetric detection of Neurotransmitters represents a cutting-edge approach in neurochemical analysis. Microfluidics allows precise manipulation of small fluid volumes, reducing reagent consumption and accelerating reactions while integrating multiple analytical steps on a single chip. Nanozyme peroxidases, mimicking natural peroxidases, provide enhanced stability and catalytic efficiency at a lower cost. The colorimetric detection mechanism signals the presence of neurotransmitters through a visible color change, making it sensitive and easy to interpret for real-time analysis. Detecting neurotransmitters like acetylcholine(ACH) is crucial for understanding and diagnosing various neurological conditions. Acetylcholine plays a key role in physiological processes such as muscle activation, memory function, and synaptic transmission. Abnormal levels are linked to disorders like Alzheimer's disease, myasthenia gravis, and Parkinson's disease. Accurate measurement aids in early diagnosis, monitoring disease progression, and evaluating treatment efficacy. A reliable detection method can advance our understanding of brain function and neurotransmitter dynamics. Real-time monitoring provides insights into how neurotransmitter fluctuations correlate with cognitive functions, behaviors, and responses to stimuli, essential for developing new therapeutic strategies and discovering novel drugs targeting neurotransmitter systems.